2019
DOI: 10.1177/1468087419878040
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency wall heat flux measurement during wall impingement of a diffusion flame

Abstract: The efficiency of internal combustion engines is limited by heat losses to the wall of the combustion chamber. A precise characterization of wall heat flux is therefore needed to optimize engine parameters. However, the existing measurements of wall heat fluxes have significant limitations; time resolution is often higher than the timescales of the physical phenomena of flame–wall interaction. Furthermore, few studies have investigated diesel flame conditions (as opposed to propagation flames). In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…This is because the increase of injection pressure can increase T inj , making fuel droplets easier to evaporate during the spraying process, thereby reducing the strength of the impingement. However, increasing P inj can increase the spray velocity and increase the intensity of turbulence near the wall, thereby increasing the heat transfer effect on the high temperature surface 37 . From the above discussion, it can be concluded that the heat transfer of spray-wall impingement can be enhanced when fuel impinges with a large injection pressure on the wall.…”
Section: Resultsmentioning
confidence: 99%
“…This is because the increase of injection pressure can increase T inj , making fuel droplets easier to evaporate during the spraying process, thereby reducing the strength of the impingement. However, increasing P inj can increase the spray velocity and increase the intensity of turbulence near the wall, thereby increasing the heat transfer effect on the high temperature surface 37 . From the above discussion, it can be concluded that the heat transfer of spray-wall impingement can be enhanced when fuel impinges with a large injection pressure on the wall.…”
Section: Resultsmentioning
confidence: 99%
“…The first possibility is that the heat transfer coefficient linked to the aerodynamic motion of the jet is higher because of the higher injection pressure and therefore a higher jet velocity, as described previously for that setup. 26 The second one is that the flame temperature is higher at the higher injection pressure. According to Tatsumi et al, 9 the flame temperature increases as the injection pressure increases.…”
Section: Resultsmentioning
confidence: 99%
“…The output from the thermocouple was amplified and filtered (10 kHz low-pass filter), and recorded with a sampling frequency of 250 kHz. The heat flux was computed using Duhamel's integral from the temperature smoothed with a Tikhonov regularization (see the literature 26 for the thermocouple data processing details). With respect to the wall temperature, the peak values were almost equal within about 5 K, however, it is visible that the shapes are different.…”
Section: Comparison Between Mems Sensor and Thermocouplementioning
confidence: 99%
“…These mechanisms are not fully understood, and several recent papers have employed advanced diagnostic techniques to resolve the relationship between heat transfer and the local turbulence in the flow. 1012 A recent study by Srna parallels the current work in that several different injection schedules were investigated in a diesel engine to understand the effect on local heat flux. 13 The experimental data set included fast-response surface temperature measurements of the cylinder liner with simultaneous optical diagnostics of the jet.…”
Section: Introductionmentioning
confidence: 85%